Exploring the iodine(III)-mediated ring contraction: new substrates, novel conditions and asymmetric reactions - Ahmad, Anees (2015)
In the first section this thesis includes the reactivity of various oxygen-containing benzofused cyclic alkenes with HTIB (Hydroxy(tosyloxy)iodobenzene). Instead of getting ring contraction products, 2H-chromene resulted in 4H-chromenes together with trans-addition products. Only cis-addition products were isolated from 4-methyl-2H-chromene. Ring contraction was observed in dihydrobenzoxepines and 2,2-dimethyl-2H-chromenes giving functionalized chromanes and benzofurans, respectively. In the second part, the ring contraction of 1,2-dihydronaphthalenes using HTIB was expanded to substrates bearing oxygen and nitrogen substituents in the aromatic ring. The N-protecting groups Fmoc and Bz are stable under the reaction conditions giving indanes in 64-77% yield. The Ts-protected substrate gave only addition products. Acetoxy and benzoyloxy alkenes afforded indanes in 60-71% yield. A new and efficient method for the oxidative rearrangement (ring contraction and expansion) of alkenes using in situ generated iodine(III) is described in the third section. The protocol uses inexpensive and stable chemicals (PhI, mCPBA and TsOH) furnishing rearrangement products in yields comparable to those obtained using commercially available iodine(III). Additionally, a new route for the one step transformation of 4-methyl-1,2-dihydronaphthalene into 1-methyl-2-tetralone using mCPBA and TsOH was developed. In the last section is presented the reactivity of chiral iodine(III) with 1,2-dihydronaphthalenes. The hypervalent iodine species is generated in situ from chiral aryl iodide, which is prepared in one high yield step from inexpensive starting materials. Protected (Ac, Bz and Fmoc) amine alkenes gave indanes in 60-75% and 58-64% ee. In the same way, oxygenated substrates afforded acetal in 41-61% yield and 54-78% ee. Ring contraction products were obtained in 77-88% yield and 34-40% ee when 1-methyl and aryl substituted alkenes were utilized.